2015
DOI: 10.3390/rs70809727
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing-Based Assessment of the Variability of Winter and Summer Precipitation in the Pamirs and Their Effects on Hydrology and Hazards Using Harmonic Time Series Analysis

Abstract: Moisture supply in the Pamir Mountains of Central Asia significantly determines the hydrological cycle and, as a result, impacts the local communities via hazards or socioeconomic aspects, such as hydropower, agriculture and infrastructure. Scarce and unreliable in situ data prevent an accurate assessment of moisture supply, as well as its temporal and spatial variability in this strongly-heterogeneous environment. On the other hand, a clear understanding of climatic and surface processes is required in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…Glaciological studies generally reported glacier retreat or glacier mass loss in the greater Pamir region [ Kääb et al ., ; Sorg et al ., ; Lutz et al ., ; Bolch et al ., ] although parts in the Pamir and the Karakoram display slight mass gain [ Gardelle et al ., ]. The spatial heterogeneity in glacier evolution in the Pamir is partly inherent from precipitation gradients and seasonality [ Fuchs et al ., ; Pohl et al ., ] although this does not account for short‐term local meteorological conditions that can play a crucial role [ Mölg et al ., ; Liu et al ., ; Khromova et al ., ]. This is important to note because the assessment of glacier evolution is often based on very few observations due to the limited availability of adequate remote sensing products.…”
Section: Introductionmentioning
confidence: 99%
“…Glaciological studies generally reported glacier retreat or glacier mass loss in the greater Pamir region [ Kääb et al ., ; Sorg et al ., ; Lutz et al ., ; Bolch et al ., ] although parts in the Pamir and the Karakoram display slight mass gain [ Gardelle et al ., ]. The spatial heterogeneity in glacier evolution in the Pamir is partly inherent from precipitation gradients and seasonality [ Fuchs et al ., ; Pohl et al ., ] although this does not account for short‐term local meteorological conditions that can play a crucial role [ Mölg et al ., ; Liu et al ., ; Khromova et al ., ]. This is important to note because the assessment of glacier evolution is often based on very few observations due to the limited availability of adequate remote sensing products.…”
Section: Introductionmentioning
confidence: 99%
“…2). Pohl et al (2015) show complex effects of weather variability on water availability and storage in the greater Pamir region. The complexity results from the interplay of temperature, precipitation amounts and timings, and resulting snow cover.…”
Section: Hydrological Cyclementioning
confidence: 99%
“…The eastern part of the River Gunt catchment spans over the dry plateau of the Tajik East Pamirs, adjacent to the above-mentioned "meteorological anomaly". The western part of the catchment can be seen as predominately westerly-influenced [43]. The same is true for the Bartang River basin north of the Gunt basin, which drains the entire Tajik South-East Pamirs before receiving the meltwaters of the Central Pamirs and the southern drainage of the Fedchenko area.…”
Section: Study Areamentioning
confidence: 51%
“…This glacio-nival dry climate is induced by westerlies-dominated moisture supply, which causes a precipitation gradient from high values in the North-West Pamir to the lowest values in the East Pamirs [42]. The arid South-East Pamirs (north of the Karakoram) are characterized by a precipitation maximum in summer, whose potential origin is the subject of controversial discussions [20,43,44]. Precipitation in the East Pamirs is said to increase (seen in Global Precipitation Climatology Project (GPCP) data [4]) and expected to trigger glacial mass gain from the West Kunlun Shan up to the Pamirs [20].…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation